Spectroscopic analysis of VVV CL001 cluster with MUSE. Issue 3 (7th April 2022) - Olivares Carvajal, J; Zoccali, M; Rojas-Arriagada, A; Contreras Ramos, R; Gran, F; Valenti, E; Minniti, J H
ABSTRACT: Like most spiral galaxies, the Milky Way contains a population of blue, metal-poor globular clusters and another of red, metal-rich ones. Most of the latter belong to the bulge, and therefore they are poorly studied compared to the blue (halo) ones because they suffer higher extinction and larger contamination from field stars. These intrinsic difficulties, together with a lack of low-mass bulge globular clusters, are reasons to believe that their census is not complete yet. Indeed, a few new clusters have been confirmed in the last few years. One of them is VVV CL001, the subject of the present study. We present a new spectroscopic analysis of the recently confirmed globular cluster VVV CL001, made by means of MUSE@VLT integral field data. Individual spectra were extracted for stars in the VVV CL001 field. Radial velocities were derived by cross-correlation with synthetic templates. Coupled with proper motions from the VVV (VISTA Variables in the Vía Láctea) survey, these data allow us to select 55 potential cluster members, for which we derive metallicities using the public code The Cannon . The mean radial velocity of the cluster is V helio = −324.9 ± 0.8 km s −1, as estimated from 55 cluster members. This high velocity, together with a low metallicity [Fe/H] = −2.04 ± 0.02 dex, suggests that VVV CL001 could be a very old cluster. The estimated distance is d = 8.23 ± 0.46 kpc, placing the cluster in the Galactic bulge. Furthermore, both its current position and the orbital parameters suggest that VVV CL001 is most probably a bulge globular cluster.